Structure of poly(L-lactic acid)s prepared by the dehydropolycondensation of L-lactic acid with organotin catalysts - Shyamroy, S.; Garnaik, Baijayantimala; Sivaram, S. (Journal of Polymer Science Part A-Polymer Chemistry, 2005)
The synthesis of low-molecular-weight (weight-average molecular weight < 45,000 g/mol) lactic acid polymers through the dehydropolycondensation of L-lactic acid was investigated. Polymerizations were carried out in solution with solvents (xylene, mesitylene, and decalin), without a solvent using different Lewis acid catalysts (tetraphenyl tin and tetra-n-butyldichlorodistannoxane), and at three different polymerization temperatures (143, 165, and 190 degrees C). The products were characterized with differential scanning calorimetry, size exclusion chromatography, vapor pressure osmometry, C-13 NMR, and matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF). The resulting polymers contained less than 1 mol % lactide, as shown by NMR. The number-average molecular weights were calculated from the ratio of the area peaks of ester carbonyl and carboxylic acid end groups via C-13 NMR. The stereosequences were analyzed by C-13 NMR spectroscopy on the basis of triad effects. Tetraphenyl tin was an effective transesterification catalyst, and the randomization of the stereosequence at 190 degrees C was observed. In contrast, the distannoxane catalyst caused comparatively less transesterification reaction, and the randomization of the stereosequences was slow even at 190 degrees C. The L-lactic acid and D-lactic acid isomers were added to the polymer chain in a small, blocky fashion. The MALDI-TOF spectra of poly(L-lactic acid) (PLA) chains doped with Na+ and K+ cations showed that the PLA chains had the expected end groups. The MALDI-TOF analysis also enabled the simultaneous detection of the cyclic oligomers of PLA present in these samples, and this led to the full structural characterization of the molecular species in PIA. (c) 2005 Wiley Periodicals, Inc.
Keywords: C-13 NMR; dehydropolycondensation; Lewis acid catalysts; MALDI; polymerization; randomization; stereosequence

Synthesis and characterization of novel value added biodegradable poly(aleuritic acid) from renewable resources(shellac) and invertible amphiphilic behaviors in various solvents - Pandey, Asutosh K.; Nande, Smita S.; Selukar, Balaji S.; Garnaik, Baijayantimala (E-Polymer, 2010)
A novel biodegradable polymer poly(aleuritic acid) (PAA) ( M̄w 120,000) was prepared from aleuritic acid, which was obtained from renewable resources (Lac) by using tin catalyst. Aleuritic acid (AL) was protected at 9, 10 position by dimethoxy propane. The protected AL (Pro.AL) was further polymerized to obtain linear protected polyaleuritic acid (PAL) by dehydropolycondensation. Effects of various kinetic and thermodynamic parameters were studied. After polymerization, the deprotection of PAL was carried out. The synthesized PAL and PAA were characterized by using various techniques such as FT-IR, LC-MS, SEC, NMR (1H and 13C), 13C CP/MAS (Cross Polarization / Magic Angle Spinning) of solid PAA, DSC, SEM and TEM etc. The micelle and inverted micelle -structure in polar and nonpolar solvents are highlighted

Environmental pollution reduction in cement industry for cocombustion of waste tyre and coal as a fuel - Patil, R. K.; Garnaik, Baijayantimala; Khond, M. P.; Nawale, L. G. (International Journal of Modern Engineering Research, 2012)
In recent years, there are several problems encountered in waste management system particularly waste tyre as well as coals. The energy generation on incineration provides large amount of polycyclic aromatic hydrocarbon (PAH) emissions which is the cause of major environmental threat. Therefore, the combustion of coal and tyre were carried out in cement industry in order to generate heat energy at 1300oC and the only remaining residue (steel powder) to enhance the strength of the cement. At the outset, the particle size of coal and tyre was cut into 63-75 and 180-212 µm respectively. Combustion experiments were conducted using Nelson reactor under controlled conditions in presence of air and also in presence of nitrogen gas (INOX) atmosphere. The temperature range was varied from 300-13000C and several fuel mass loading in the furnace, expressed in terms of bulk equivalence ratios in the range of 0.7-2.4. At fixed bulk equivalence ratios, as the furnace gas (Air) temperature increased the polycyclic aromatic hydrocarbon yields from both fuels decreased drastically, while the CO2 yields increased. At the highest temperature around 13000C, the effluent of combustion of both (coal and tyre) fuels was practically devoid of polycyclic aromatic hydrocarbon (PAH) (at a detection limit of 0.3 µg of a PAH component/g of fuel burnt). In order to understand the rate of thermal effect and morphology of co combustion material (coal and tyre), the preliminary results are very essential to explore. Therefore, the thermo gravimetric analysis (TGA) and environmental scanning electron microscopy (ESEM) were carried out and results of coal and tyre mixture at various temperature conditions will be highlighted.

Novel solid cloisite tin catalyzed polymerization of L-lactide - Selukar, Balaji Sidram; Pandey, Asutosh Kumar; Nande, Smita Sunil; Bansode, Avinash Santram; Garnaik, Baijayantimala (Journal of Chemistry and Chemical Engineering, 2012)
A novel cloisite modified solid catalyst was prepared in a single step from commercially available starting materials for the first time. The ring opening polymerization of L-lactide and D-lactide using this cloisite modified solid catalyst resulted in homopolymers of 75,000 and PDI = 1.6 and the maximum molecular weight (Mw) i.e. 180,000 with PDI = 1.9 were obtained. The catalytic activity of cloisite modified solid catalyst was compared with the conventional stannous octoate catalyst and found superior to stannous octoate in all respect such as conversion, molecular weight and molecular weight distribution etc.. Moreover, the maximum molecular weight i.e. 180,000was obtained at 220 o C, whereas, transesterification reaction predominate in presence of stannous octoate. The linear structure was confirmed by quantitative 13C NMR Spectroscopy. Blend films were obtained by casting mixed solutions of poly (D-lactide) and poly (L lactide) at various compositions, and stereocomplex was formed at 50/50 composition with molecular weight of 75,000.

Synthesis of linear polylactic acid –based urethanes using tin modified closite -30b catalyst - Selukar, Balaji S.; Parwe, Sharad P.; Mohite, Kavita K.; Garnaik, Baijayantimala (Advance Material Letters, 2012)

Copolymerization of aleuritic acid with l-lactic acid and study the aggregation behavior in different solvents - Pandey, Asutosh K.; Garnaik, Baijayantimala (International Journal of Research in Pharmacy and Chemistry, 2013)
In this present work, we highlight the copolymerization of L-lactic acid (L-LA with protected aleuritic acid in presence of Lewis acid catalyst using dehyropolycondensation method. The resulted copolymers are pliable, soft, waxy or even viscous liquid copolymers influenced by the aleuritic acid content. The purpose of this study is to investigate the physical properties. In addition, deprotected copolymers focus micelle-like aggregates in various organic solvents and mixed organic solvent at various proportions.

PEEK/SiO2 composites with high thermal stability for electronic applications - Goyal, R. K.; Rokade, K. A.; Kapadia, A. S.; Selukar, B. S.; Garnaik, Baijayantimala (Electronic Materials Letters, 2013)
Thermal and mechanical properties of new high performance polymer matrix composites based on poly(etheretherketone) (PEEK) as matrix and crystalline-silica (SiO2) as reinforcement were discussed for application in electronic packaging substrates or printed circuit boards. The content of SiO2 was varied between 0 and 50 wt. %. Scanning electron microscopy showed uniform dispersion of SiO2 particles in the matrix. Thermogravimetry analysis showed significant increase in thermal stability and char yield with increase in SiO2 content in the matrix. Differential scanning calorimetry showed that SiO2 had a heterogeneous nucleating effect on PEEK, leading to an increase in peak temperature of crystallization and onset crystallization temperature of the composites compared to a pure matrix. The microhardness increased approximately 42%. A modified rule of mixtures with a strengthening efficiency factor equal to 0.06 fit the data nicely. The results show that the prepared PEEK/SiO2 composites may have potential applications in electronics.
Keywords: hardness; PEEK; polymer matrix composites; Thermal properties

Study of grafting of polylactic acid and its copolymer with 12-hydroxy stearic acid on the surface of MWCNT by 13CCP/MAS and AFM - Pandey, Asutosh K.; Garnaik, Baijayantimala (International Journal of Research in Pharmacy and Chemistry, 2013)
The purpose of this study to study the structure property relationship of grafted material on MWCNT, the determination of NMR nuclei spin-lattice (T1) and spin-spin (T2) relaxation times suggest that the broaden signals are associated with diamagnetic species namely the nanotube attached polymer moieties. the AFM image of PLA oligomer grafted MWCNTs and topography patterns comprised of height from 0-250 nm and the side lengths ranging from 0.0 to 7.7 µm. Surface patches are formed randomly distributed employing that the presence of side chain hanged at 12-postion in the copolymer grafted on MWCNTs.

Synthesis of ciprofloxacin-conjugated poly(L-lactic acid) polymer for nanofiber fabrication and antibacterial evaluation - Parwe, Sharad P.; Chaudhari, Priti N.; Mohite, Kavita K.; Selukar, Balaji S.; Nande, Smita S.; Garnaik, Baijayantimala (International Journal of Nanomedicine, 2014)
Ciprofloxacin was conjugated with polylactide (PLA) via the secondary amine group of the piperazine ring using PLA and 7-(4-(2-Chloroacetyl) piperazin-1-yl)-1-cyclopropyl-6-fluoro-1, 4-dihydro-4-oxoquinoline-3-carboxylic acid. Zinc prolinate, a biocompatible catalyst was synthesized, characterized, and used in ring opening polymerization of L-lactide. Five different kinds of OH-terminated poly(L-lactide) (two-, three-, four-, six-arm, star-shaped) homopolymers were synthesized by ring opening polymerization of L-lactide in the presence of dodecanol, glycerol, pentaerythritol, dipentaerythritol as initiator and zinc prolinate as a catalyst. The structures of the polymers and conjugates were thoroughly characterized by means of gel permeation chromatography, matrix-assisted laser desorption/ionization-time of flight mass spectrometry, and nuclear magnetic resonance spectroscopy. PLA (molecular weight = 100,000) and ciprofloxacin conjugated PLA were used for fabrication of nonwoven nanofiber mat (diameter ranges; 150-400 nm) having pore size (62-102 nm) using electrospinning. The microbiological assessment shows that the release of ciprofloxacin possesses antimicrobial activity. The drug-release behavior of the mat was studied to reveal potential application as a drug delivery system. The result shows that the ciprofloxacin release rates of the PLA conjugate nonwoven nanofiber mat could be controlled by the drug loading content and the release medium. The development of a biodegradable ciprofloxacin system, based on nonwoven nanofiber mat, should be of great interest in drug delivery systems.
Keywords: antibacterial activity; ciprofloxacin conjugated polylactides; CP-PLA; drug release; electrospinning; MDR; nonwoven nanofibers; zinc prolinate

High molecular weight polylactic acids by polyesterification using diisopropylcarbodiimide (DIPC) and 4-(dimethylamino) pyridinium ptoluene sulfonate (DPTS) - Shyamroy, S.; Garnaik, Baijayantimala; Sivaram, S. (Polymer Bulletin, 2015)
High molecular weight poly(l-lactic acid) has been prepared from the corresponding functionally terminated oligomers employing a polyesterification method at room temperature using diisopropylcarbodiimide and 4-(dimethylamino) pyridinium-p-toluene sulfonate. Self-condensation of hydroxyl and carboxylic acid-terminated poly(l-lactic acid) oligomers (M (n) : similar to 1,000) resulted in polymers with high molecular weights (M (n) > 45,000) under mild conditions. End-group analysis by MALDI-TOF provided evidence for N-acylurea formation in the product under the reaction conditions employed.

Investigation of the biocompatibility and cytotoxicity associated with ROP initiator and its role in bulk polymerization of L-lactide - Parwe, Sharad P.; Warkad, Shrikant D.; Mane, Manoj V.; Shedage, Pranita S.; Garnaik, Baijayantimala (Polymer, 2017)
Poly (L-lactide) (PLLA) is one of the most attractive polymers for use in biomedical applications. In such applications it is necessary to reduce the use of toxic chemicals and catalysts used in PLLA synthesis, to minimize any adverse effects. In view of this, we have performed ring opening polymerization (ROP) of Llactide (LA) using biocompatible initiator, namely, Zinc L-Proline (ZnP) in bulk. High molecular weight PLLA (Mw up to 1.45 x 10(5) Da) was obtained using the ZnP complex. The ZnP complex is safe, easy to prepare, store and handle. H-1 and C-13 NMR spectra of PLLA were used to determine the extent of monomer conversion and stereo sequence respectively. Differential Scanning Calorimetry (DSC) and Size Exclusion Chromatography (SEC) were used to determine thermal properties, Mn, Mw and polydispersity index respectively. The mechanism of ROP of LA in the presence of ZnP was studied using Density Functional Theory (DFf) which was in good agreement with results from H-1 NMR and Matrix-Assisted Laser Desorption/Ionization Spectrometry (MALDI-TOF). Biocompatibility/non toxicity of PLLA prepared using ZnP was studied in-vitro using MTT assay by examining the proliferation rate of mouse myoblast C2C12 cell line. Escherichia coli and Staphylococcus aureus were used for the study of antibacterial activity of PLLA. (C) 2017 Elsevier Ltd. All rights reserved.

Organo-clay hybrid hydrophobic spherical styrene divinylbenzene crosslink beads for high-performance carbon dioxide capture - Nande, Smita S.; Garnaik, Baijayantimala (New Journal of Chemistry, 2017)
Herein, we report carbon dioxide sorption properties for a series of cloisite-containing crosslink hybrid materials. These materials were prepared by copolymerizing styrene divinylbenzene in the presence of various cloisites through suspension polymerization in one pot to obtain uniform spherical beads. The homopolymer formed during the polymerization was separated from the hybrid. The synthetic strategy is user-friendly and cost-effective, can be easily scaled up for production, and provides materials with good mechanical strength. The microporous polymeric spheres containing organo-clay (cloisite) showed a high surface area of similar to 80-370 m(2) g(-1) with a microsphere size of similar to 4.4 nm. These polymeric spherical beads were hydrophobic and thermally stable up to 300 degrees C. They showed high carbon dioxide uptake (up to similar to 20.7 wt% at 273 K/1.0 bar) due to lone pair electrons of heteroatom, which might sharpen the interaction between the CO2 molecules and polymeric matrices through local dipole/quadruple interaction. Moreover, they showed good capacity to store CO2 due to the presence of quaternary ammonium groups in the clay and a large amount of narrow microspheres (B4.4 nm). The equilibrium CO2 capacities of the prepared spherical beads were due to the interaction between quaternary ammonium and the negatively charged oxygen atoms of CO2, and these spherical beads showed potential applications in gas adsorption and separation.

Fast dissolving moxifloxacin hydrochloride antibiotic drug from electrospun Eudragit L-100 nonwoven nanofibrous mats - Giram, Prabhanjan S.; Shitole, Ajinkya; Nande, Smita S.; Sharma, Neeti; Garnaik, Baijayantimala (Materials Science & Engineering C-Materials For Biological Applications, 2018)
Antimicrobial electrospun nonwoven Eudragit L-100 nanofibrous mats containing Moxifloxacin hydrochloride (MOX-HCL) were fabricated for fast dissolving drug delivery systems (DDSs) associated with wound infection. The morphological characterization of nanofibers using ESEM revealed that the average diameter of non-woven nanofibrous mats ranges 200-600 nm. The nanofiber showed cylindrical shape with crack on the surface. Differential scanning calorimetric (DSC) and Wide Angle X-ray diffraction (WAXRD) demonstrate that the drug exists in an amorphous state in the nanofibers. Nanofibrous mats were also tested for mechanical strength, contact angle, swelling assay, haemolysis and disintegration test. In vitro disintegration tests demonstrated that the dissolution of Eudragit L-100 fiber mats was within 25 s which was higher compared to the pure drug. The Eudragit nanofibers showed pH-dependent drug release profiles, with slow release at pH 1.2 and burst release (around 30 s) at pH 6.8. The in-vitro quantitative and qualitative antimicrobial assay showed that the developed Eudragit L-100 nanofibrous mats with MOX-HCL concentration of 1%, 5% and 15 wt% exhibited antibacterial activities against both gram positive (Staphylococcus aureus) and gram negative (Escherichia coli) bacteria. The invitro cytotoxicity assay using mouse fibroblast NIH/3T3 cells demonstrated significant biocompatibility of nanofiber mats. As per the results of biological evaluation, Eudragit L-100 nanofibrous mats with 1wt% MOX-HCL could be a suitable substrate for biomedical applications. Eudragit L-100 nanofibrous mats containing Moxifloxacin hydrochloride (MOX-HCL) showed immediate DDSs for localized drug release in the wound infection at slightly acidic or alkaline conditions where faster drug release rate is required for wound healing.

Clopidogrel eluting electrospun polyurethane/polyethylene glycol thromboresistant, hemocompatible nanofibrous scaffolds - Shitole, Ajinkya A.; Giram, Prabhanjan S.; Raut, Piyush W.; Rade, Priyanka P.; Khandwekar, Anand P.; Sharma, Neeti; Garnaik, Baijayantimala (Journal of Biomaterials Applications, 2019)
Biomaterials used as blood-contacting material must be hemocompatible and exhibit lower thrombotic potential while maintaining hemostasis and angiogenesis. With the aim of developing thromboresistant, hemocompatible nanofibrous scaffolds, polyurethane/polyethylene glycol scaffolds incorporated with 1, 5, and 10 wt% Clopidogrel were fabricated and evaluated for their physiochemical properties, biocompatibility, hemocompatibility, and antithrombotic potential. The results of physicochemical characterization revealed the fabrication of nanometer-sized scaffolds with smooth surfaces. The incorporation of both polyethylene glycol and Clopidogrel to polyurethane enhanced the hydrophilicity and water uptake potential of polyurethane/polyethylene glycol/Clopidogrel scaffolds. The dynamic mechanical analysis revealed the enhancement in mechanical strength of the polyurethane/polyethylene glycol scaffolds on incorporation of Clopidogrel. The polyurethane/polyethylene glycol/Clopidogrel scaffolds showed a tri-phasic drug release pattern. The results of hemocompatibility assessment demonstrated the excellent blood compatibility of the polyurethane/polyethylene glycol/Clopidogrel scaffolds, with the developed scaffolds exhibiting lower hemolysis, increased albumin and plasma protein adsorption while reduction in fibrinogen adsorption. Further, the platelet adhesion was highly suppressed and significant increase in coagulation period was observed for Clopidogrel incorporated scaffolds. The results of cell adhesion and cell viability substantiate the biocompatibility of the developed nanofibrous scaffolds with the HUVEC cell viability on polyurethane/polyethylene glycol, polyurethane/polyethylene glycol/Clopidogrel-1, 5, and 10% at day 7 found to be 12.35, 13.36, 14.85, and 4.18% higher as compared to polyurethane scaffolds, and the NIH/3T3 cell viability found to be 35.27, 70.82, 36.60, and 7.95% higher as compared to polyurethane scaffolds, respectively. Altogether the results of the study advocate the incorporation of Clopidogrel to the polyurethane/polyethylene glycol blend in order to fabricate scaffolds with appropriate antithrombotic property, hemocompatibility, and cell proliferation capacity and thus, might be successfully used as antithrombotic material for biomedical application.
Keywords: adhesion; cardiovascular; coagulation; electrospinning; Hemocompatible; platelet

Electrospun polycaprolactone/hydroxyapatite/ZnO nanofibers as potential biomaterials for bone tissue regeneration - Shitole, Ajinkya A.; Raut, Piyush W.; Sharma, Neeti; Giram, Prabhanjan; Khandwekar, Anand P.; Garnaik, Baijayantimala (Journal of Materials Science-Materials In Medicine, 2019)
Fabricating a bioartificial bone graft possessing structural, mechanical and biological properties mimicking the real bone matrix is a major challenge in bone tissue engineering. Moreover, the developed materials are prone to microbial invasion leading to biomaterial centered infections which might limit their clinical translation. In the present study, biomimetic nanofibrous scaffolds of Poly -caprolactone (PCL)/nano-hydroxyapatite (nHA) were electrospun with 1wt%, 5wt%, 10wt%, 15wt% and 30wt% of zinc oxide (ZnO) nanoparticles in order to understand the optimal concentration range of (ZnO) nanoparticles balancing both biocompatibility and osteoregeneration. The developed nanofibrous scaffolds were successfully characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDAX), contact angle, fourier transform infrared spectroscopy (FTIR), wide-angle X-Ray diffraction (WAXD), brunaueremmett Teller (BET) surface area and tensile testing. Biocompatibility of the developed scaffolds at in vitro level was evaluated by culturing MG-63 cells and investigating the impact on cell viability, proliferation, protein adsorption, alkaline phosphatase (ALP) activity and biomineralization. The PCL/nHA scaffolds exhibited a 1.2-fold increase in cell viability and proliferation, while incorporation of ZnO nanoparticles to PCL/nHA imparted antimicrobial activity to the scaffolds with a progressive increase in the antimicrobial efficacy with increasing ZnO concentration. The results of cell viability were supported by ALP activity and mineralization assay, wherein, PCL/nHA/ZnO scaffolds showed higher ALP activity and better mineralization capacity as compared to pristine PCL. Although, the PCL/nHA/ZnO scaffolds with 10, 15 and 30wt% of ZnO particles exhibited superior antimicrobial efficacy against both gram-negative (E. coli) and gram-positive (S. aureus) bacteria, a significant decrease in the cell viability and mechanical properties was observed at higher concentrations of ZnO namely 15 and 30%. Amongst the various ZnO concentrations studied optimal cell viability, antimicrobial effect and mechanical strength were observed at 10wt.% ZnO concentration. Thus, the present study revealed that the biomimetic tri-component PCL/nHA/ZnO scaffolds with ZnO concentration range of10% could be ideal for achieving optimal biocompatibility (cell proliferation, biomineralization, and antimicrobial capacity) and mechanical stability thus making it a promising biomaterial substrate for bone tissue regeneration. [GRAPHICS] .

Kinetic and biocompatibility investigation on the catalytic ring opening polymerization of L-lactide in bulk using cyclic Bu2Sn initiators derived from ethylene glycol, pentaerythritol and cloisite 30B - Mohite, Kavita K.; Garnaik, Baijayantimala (Polyhedron, 2020)
In the present work, considering a green approach, PLLA was synthesized by the ring-opening polymerization of L-LA using various cyclic initiators (2,2-dibutyl-2-stanna-1,3-dioxacyclo ethane (1), spirocyclic tin (3) and cloisite modified tin (5)). PLLA was characterized by size exclusion chromatography, differential scanning calorimetry, H-1 and C-13 NMR, XRD and MALDI-TOF. The molecular weight distribution was narrow (<1.5) for both low and high molecular weights (>85,000 g/mol). An X-ray study showed the crystalline nature of PLLA, irrespective of the different types of initiators and polymerization conditions. A kinetic investigation showed that all polymerizations were first order with respect to the monomer and no termination reactions occurred during the polymerization. MALDI-TOF spectra of PLLA chains doped with Na+ and K+ cations show that the PLLA prepared using initiators 1 and 3 have hydroxyl and carboxyl end groups without incorporation of tin. The MALDI-TOF spectrum of PLLA prepared using initiator 5 also enabled the simultaneous detection of the linear and cyclic structure of PLLA without tin. Biocompatible and biodegradable PLLA was obtained, which could be used for biomedical applications. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Cloisite modified tin; Cyclic tin initiator; MALDI-TOF; Poly (L-Lactide); Spirocyclic

LHRH-conjugated, PEGylated, poly-lactide-co-glycolide nanocapsules for targeted delivery of combinational chemotherapeutic drugs Docetaxel and Quercetin for prostate cancer - Shitole, Ajinkya A.; Sharma, Neeti; Giram, Prabhanjan; Khandwekar, Anand; Baruah, Meghna; Garnaik, Baijayantimala; Koratkar, Santosh (Materials Science & Engineering C-Materials for Biological Applications, 2020)
One of the major challenges in effective cancer chemotherapy is the severe systemic cytotoxicities of anticancer drugs on healthy tissues. The present study reports chemically modified polymeric nanocapsules (NCs) encapsulating combination of chemotherapeutic drugs Docetaxel (DTX) and Quercetin (QU) for its active targeting to prostate cancer (PCa). The active targeting was achieved by conjugating Luteinizing-hormone-releasing hormone (LHRH) ligand to poly-lactide-co-glycolide (PLGA) using polyethylene glycol (PEG) as a spacer. The structure of the conjugates was characterized and confirmed using H-1 NMR and ATR-FTIR. The drug encapsulated NCs showed a homogenous size distribution with their size ranging between 120 and 150 nm, and exhibited a negative zeta potential in the range of - 20 to - 40 mV. The in vitro release studies highlighted the sustained drug release pattern from the respective NCs; while the PEG coating to polymeric NCs provided serum stability to the NCs. The in vitro biological evaluation of the NCs was conducted using PC-3 and LNCaP cell lines. The results of the cellular uptake studies showed a significantly higher untake of the LHRH targeted NCs, while the LHRH-targeted-PEGylated DTX: QU NCs exhibited higher caspase-3 activity. The cell viability assay results showed the enhanced cell inhibition activity of the combinatorial DTX: QU when compared to individual DTX. Further, higher cell cytotoxicity was achieved by LHRH-targeted DTX: QU NCs as compared to their free-form or non-targeted NCs. Finally, the results of in vivo tumor localization and in vivo antitumor activity studies complimented and upheld the in vitro results, demonstrating the beneficial role of PLGA-PEG-LHRH NCs encapsulating combination of DTX and QU in combating prostate cancer (PCa).
Keywords: Active targeting; Anticancer; Controlled release; EPR effect; Hydrophobic; Prostate

Ofloxacin-loaded PLLA nanofibrous mats for wound dressing applications - Rade, Priyanka P.; Garnaik, Baijayantimala (ACS Applied Bio Materials, 2020)
Poly(l-lactide) (PLLA) was synthesized from l-lactide in the presence of a zinc salen complex. Ofloxacin (OFLX)-loaded PLLA nanofibrous mats were fabricated by electrospinning using dichloromethane/dimethyl sulfoxide (4:1 v/v) solutions containing different amounts of OFLX (1, 3, 5, and 10 w/w%). The morphology and diameter of nanofibrous mats were studied by scanning electron microscopy (SEM). The internal morphology of the nanofibers was examined by transmission electron microscopy (TEM). Miscibility between OFLX and PLLA in nanofibrous mats was confirmed by attenuated total reflection–Fourier transform infrared (ATR–FTIR) spectroscopy. Differential scanning calorimetry (DSC) confirmed the interaction of OFLX with PLLA nanofibrous mats. The presence of OFLX in PLLA nanofibrous mats increased the tensile strength significantly, which was confirmed by dynamic mechanical analysis (DMA). The in vitro drug release profile was studied at pH values 4.6, 5.8, and 7.4. OFLX-loaded PLLA nanofibrous mats showed burst release till first 12 h, and sustained release followed up to 168 h. The in vitro biocompatibility test of nanofibrous mats was carried out using the 3-(4,5-dimethylthiazol-2yl)-2,5-diphenyl tetrazolium bromide (MTT) assay against the NIH/3T3 fibroblast cell line. The results of MTT assay demonstrated cell viability and cell proliferation at a concentration as low as 10 w/w%, which proved their nontoxicity and biocompatibility. OFLX-loaded PLLA nanofibrous mats exhibited good antibacterial activity against Staphylococcus aureus and Escherichia coli. The in vivo wound healing study on rats showed 44, 65, and 88% wound closure rates on 14th day with control, PLLA, and OFLX-loaded PLLA nanofibrous mats, respectively. The results proved that the PLLA nanofibrous mats loaded with an appropriate concentration of OFLX are promising candidates for wound dressing applications.
Keywords: nanofibers nontoxic biocompatible; PLLA ofloxacin; wound dressing

Poly (vinylpyrrolidone)-iodine engineered poly (epsilon-caprolactone) nanofibers as potential wound dressing materials - Shitole, Ajinkya A.; Raut, Piyush; Giram, Prabhanjan; Rade, Priyanka; Khandwekar, Anand; Garnaik, Baijayantimala; Sharma, Neeti (Materials Science & Engineering C-Materials for Biological Applications, 2020)
Facilitating the process of wound healing and effective treatment of wounds remains a serious challenge in healthcare. Wound dressing materials play a major role in the protection of wounds and in accelerating the natural healing process. In the present study, novel core/shell (c/s) nanofibrous mats of poly(vinyl pyrrolidone)-iodine (PVPI) and polycaprolactone (PCL) were fabricated using a co-axial electrospinning process followed by their surface modification with poly-L-lysine. The developed nanofibrous mats were extensively characterized for their physicochemical properties using various analytical techniques. The core/shell structure of the PVP-I/PCL nanofibers was confirmed using TEM analysis. The PVP-I release studies showed an initial burst phase followed by a sustained release pattern of PVP-I over a period of 30 days. The developed nanofibers exhibited higher BSA and fibrinogen adsorption as compared to pristine PCL. Cytotoxicity studies using MTT assay demonstrated that the PVP-I/PCL (c/s) nanofibers were cytocompatible at optimized PVP-I concentration (3 wt%). The PCL-poly-L-lysine and PVP-I/PCL-poly-L-lysine nanofibers exhibited higher cell viability (24.2% and 21.4% higher at day 7) when compared to uncoated PCL and PVP-I/PCL nanofibers. The PVP-I/PCL nanofibers showed excellent antimicrobial activity against both Gram-positive (S. aureus) and Gram-negative (E. coli) bacteria. The inflammatory response of Mouse RAW 264.7 macrophage cells towards the nanofibers was studied using RTPCR. It revealed that the pro-inflammatory cytokines (TNF-alpha and IL-1 beta) were significantly upregulated on PCL nanofibers, while their expression was comparatively lower on poly-L-lysine coated PCL or PVP-I/PCL(c/s) nanofibers. Overall, the study highlights the ability of poly-L-lysine coated PVP-I/PCL (c/s) nanofibers as potential wound dressing materials effectively facilitating the early stage wound healing and repair process by virtue of their selective modulation of inflammation, cell adhesion and antimicrobial properties.
Keywords: biodegradable; Controlled release; Core/shell; electrospinning; scaffolds; tissue engineering

Synthesis and characterization of biocompatible poly (L-lactide) using zinc (II) salen complex - Rade, Priyanka P.; Garnaik, Baijayantimala (International Journal of Polymer Analysis and Characterization, 2020)
A biocompatible zinc (II) complex based on a tetradentate N,N,O,O-type salen ligand was synthesized, characterized and used for the solvent-free ring-opening polymerization (ROP) of L-lactide in bulk at 180 degrees C to prepare high molecular weight poly(L-lactide) (M-n: 82,600 Da;M-w: 140,000 Da; PDI: 1.70). Poly(L-lactide) (PLLA) was characterized using FTIR,H-1 NMR,C-13 NMR, GPC, TGA, DSC, WAXD, and MALDI-ToF. Kinetic measurement was carried out and first-order behavior to monomer was observed. Thek(app)was found as 6 +/- 0.001 x 10(-4 )s(-1). The biocompatibility of the PLLA was confirmed byin vitrocytotoxicity against NIH/3T3 fibroblast cell line and can be used in biomedical applications.
Keywords: Biocompatible; Biomedical Applications; in vitro; PLLA; zinc (II) salen complex

Evaluation of biocompatibility of synthesized low molecular weight PLGA copolymers using zinc L-proline through green route for biomedical application - Giram, Prabhanjan S.; Garnaik, Baijayantimala (Polymers for Advanced Technologies, 2021)
Poly(lactide-co-glycolide) (PLGA) copolymers were synthesized by ring opening polymerization in presence of zinc proline and stannous octoate in bulk through green route and were designated as PLGA-1 and PLGA-2 respectively. These copolymers were characterized using NMR, SEC, DSC, X-ray and MALDI-TOF analysis. For the first time, the low molecular weight of PLGA (similar to 11,000 Da) was mainly targeted to explore acute oral toxicity in the presence of zinc L-proline and stannous octoate. The haemolysis and cell viability assay were carried out for in-vitro cytotoxicity assessment. Haemolysis assay of PLGA-2 was confirmed and haemolytic potential exceeded limit of American society of testing of material standard. The cell viability study using fibroblast cell lines (NIH3T3), exhibited statistically significant difference in results between PLGA-1 and PLGA-2. The acute toxicity study was performed in Balb/c mice for biomarker, hematological and histopathological analysis. No mortality was observed during the entire observation period, and no macroscopic change of the organs was observed in PLGA-1 treated group where PLGA-2 treated group showed sign of toxicity. The results obtained from in-vitro and in-vivo studies suggested that PLGA-2 was toxic whereas PLGA-1 was nontoxic in nature. Therefore, PLGA-1 can be regarded as biocompatible biomaterials for potential for drug delivery and biomedical application.
Keywords: OECD-420; poly (lactide-co-glycolide); ring opening polymerization; Stannous octoate; zinc L-Proline

Green synthesis of methoxy-poly(ethylene glycol)-block-poly(l-lactide-co-glycolide) copolymer using zinc proline as a biocompatible initiator for irinotecan delivery to colon cancer in vivo - Giram, Prabhanjan S.; Wang, Julie Tzu-Wen; Walters, Adam A.; Rade, Priyanka P.; Akhtar, Muhammad; Han, Shunping; Faruqu, Farid N.; Abdel-Bar, Hend M.; Garnaik, Baijayantimala; Al-Jamal, Khuloud T. (Biomaterials Science, 2021)
Poly(lactic-co-glycolic acid) (PLGA) is the most commonly described biocompatible copolymer used in biomedical applications. In this work, a green synthetic approach based on the biocompatible zinc proline complex, as an initiator for PLGA synthesis, is reported for the first time for the synthesis of methoxy-poly(ethylene glycol)-block-poly(l-lactic-co-glycolic acid) (mPEG-PLGA). mPEG-PLGA with controlled molecular weight and narrow polydispersity was synthesised. Its potential for delivery of irinotecan (Ir), a poorly water-soluble chemotherapeutic drug used for the treatment of colon and pancreatic cancer, was studied. Nanoparticles of controlled size (140-160 nm), surface charge (similar to-10 mV), release properties and cytotoxicity against CT-26 (colon) and BxPC-3 (pancreatic) cancer cells, were prepared. Tumor accumulation was confirmed by optical imaging of fluorescently labelled nanoparticles. Unlike Tween (R) 80 coated NP-Ir, the Pluronic (R) F-127 coated NP-Ir exhibits significant tumor growth delay compared to untreated and blank formulation treated groups in the CT-26 subcutaneous tumor model, after 4 treatments of 30 mg irinotecan per kg dose. Overall, this proof-of-concept study demonstrates that the newly synthesized copolymer, via a green route, is proven to be nontoxic, requires fewer purification steps and has potential applications in drug delivery.

Physicochemical and in vitro antibacterial evaluation of metronidazole loaded eudragit S-100 nanofibrous mats for the intestinal drug delivery - Rade, Priyanka P.; Giram, Prabhanjan S.; Shitole, Ajinkya A.; Sharma, Neeti; Garnaik, Baijayantimala (Advanced Fiber Materials, 2021)
Metronidazole (MTZ) loaded Eudragit S-100 (ES-100) nonwoven nanofibrous mats were successfully electrospun and evaluated for intestinal drug delivery. MTZ was varied in the range of 1–15% (w/w) in ES-100 nanofibrous mats, the morphological characterization of nanofibrous mats was carried out using FE-SEM and the average diameter of nanofiber was found in the range 150–600 nm. WAXD and DSC demonstrated the amorphous nature of MTZ in ES-100 nanofibrous mats. Their contact angle analysis confirmed the hydrophobic nature. The mechanical strength of ES-100 nanofibrous mats decreased with increasing MTZ concentration. The drug release profiles showed 74% MTZ release from ES-100d within 2 h at pH 6.8 which is the colonic environment. Antibacterial activities against gram-positive bacteria (Staphylococcus aureus) and gram-negative bacteria (Escherichia coli) showed that the ES-100 nanofibrous mats loaded with MTZ exhibited good activity.

Toughening poly(l-lactide) blends: effectiveness of sequence-controlled six-arm star-branched block copolymers of poly(L-lactide) and poly(epsilon-caprolactone) - Deokar, Megha D.; Garnaik, Baijayantimala; Sivaram, Swaminathan (ACS Omega, 2022)
Well-defined six-arm star-branched bio-degradable block copolymers of L-lactide and epsilon-caprolactone were prepared using controlled ring-opening polymerization and a sequential monomer addition method using dipentaerythritol as the initiator core and organocatalysts at low temperatures in solution. Sequence of enchainment was changed by reversing the order of monomer addition giving, either, a crystalline PLA block or an amorphous PCL block as the outer segment. Well-defined six-arm poly(epsilon-caprolactone-b-L-lactide, 6s-PCL-b-PLA) block copolymers were obtained with a range of segment molecular weights. However, in the case of six-arm poly(L-lactide-b-epsilon-caprolactone, 6s-PLA-b-PCL), disruption of the block structure was observed on account of competing transesterification reactions accompanying a chain-growth reaction. Such sequence-controlled block copolymers showed interesting phase morphologies, as evidenced by differential scanning calorimetry (DSC) studies. 6s-PCL-b-PLA showed two glass-transition temperatures and two melting temperatures characteristic of the amorphous and crystalline blocks. 6s-PCL-b-PLA and 6s-PLA-b-PCL with different segment chain lengths were solution blended (10 wt %) with a commercially sourced PLA. All the blends were highly transparent. The structure and properties of the blend were examined by DSC, measurement of mechanical properties, and scanning electron microscopy. The results show that a phase-separated 6s-PCL-b-PLA copolymer results in two- to three-fold improvement in tensile toughness without the loss of modulus. A possible hypothesis for the mechanism of tensile toughness in the blend has been proposed.

Engineered PLGA core-lipid shell hybrid nanocarriers improve the efficacy and safety of irinotecan to combat colon cancer - Giram, Prabhanjan S.; Nimma, Ramakrishna; Bulbule, Anuradha; Yadav, Amit Singh; Gorain, Mahadeo; Radharani, Nalukurthi Naga Venkata; Kundu, Gopal C.; Garnaik, Baijayantimala (ACS BIOMATERIALS SCIENCE & ENGINEERING, 2024)
Keywords: BULK-POLYMERIZATION; Drug-delivery; LIPOSOMAL DOXORUBICIN

Poly(d,l-lactide-co-glycolide) surface-anchored biotin-loaded irinotecan nanoparticles for active targeting of colon cancer - Giram, Prabhanjan S.; Nimma, Ramakrishna; Bulbule, Anuradha; Yadav, Amit Singh; Gorain, Mahadeo; Radharani, Nalukurthi Naga Venkata; Kundu, Gopal C.; Garnaik, Baijayantimala (ACS Omega, 2024)
A poly-(d,l-lactide-co-glycolide) (PLGA) copolymer was synthesized using the ring-opening polymerization of d,l-lactide and glycolide monomers in the presence of zinc proline complex in bulk through the green route and was well characterized using attenuated total reflectance-Fourier transform infrared, H-1 and C-13 nuclear magnetic resonance, gel permeation chromatography, differential scanning calorimetry, X-ray diffraction, matrix-assisted laser desorption/ionization time-of-flight, etc. Furthermore, PLGA-conjugated biotin (PLGA-B) was synthesized using the synthesized PLGA and was employed to fabricate nanoparticles for irinotecan (Ir) delivery. These nanoparticles (PLGA-NP-Ir and PLGA-B-NP-Ir) were tested for physicochemical and biological characteristics. PLGA-B-NP-Ir exhibited a stronger cellular uptake and anticancer activity as compared to PLGA-NP-Ir in CT-26 cancer cells (log p < 0.05). The accumulation and retention of fluorescence-labeled nanoparticles were observed to be better in CT-26-inoculated solid tumors in Balb/c mice. The PLGA-B-NP-Ir-treated group inhibited tumor growth significantly more (log p < 0.001) than the untreated control, PLGA-NP-Ir, and Ir-treated groups. Furthermore, no body weight loss, hematological, and blood biochemical tests demonstrated the nanocarriers' nontoxic nature. This work presents the use of safe PLGA and the demonstration of a proof-of-concept of biotin surface attached PLGA nanoparticle-mediated active targeted Ir administration to combat colon cancer. To treat colon cancer, PLGA-B-NP-Ir performed better due to specific active tumor targeting and greater cellular uptake due to biotin.

Synthesis of amine-loaded styrene–divinylbenzene copolymers for carbon dioxide capture - Nande, Smita S.; Garnaik, Baijayantimala (ACS Engineering Au, 2025)
Carbon dioxide capture by various tertiary amines and quaternary bulky ammonium salts loaded in cross-link hybrid polymer (styrene–divinylbenzene copolymer) was explored. These polymeric materials were prepared by suspension polymerization in one pot using monomers like styrene and divinylbenzene in the presence of various amines to obtain uniform spherical beads. The homopolymer was separated from the cross-link hybrid product by Soxhlet extraction. The synthetic strategy is cost-effective and user-friendly, can be easily scaled up for production, and confirms better mechanical strength. The amine-loaded microporous polymeric spheres displayed a microsphere size of 5.2 nm with a high surface area of ∼25–310 m2 g–1. These hydrophobic polymeric spherical beads were thermally stable up to 200 °C. The quaternary ammonium group salt (bulky)-loaded beads presented high carbon dioxide uptake (up to ∼16.4 wt % at 273 K /1.0 bar) due to the presence of lone pair electrons of the heteroatom, which might improve the interaction between the polymeric matrices and CO2 molecules through local-dipole/quadruple interactions. In the case of tertiary amines, a high uptake of carbon dioxide (up to ∼15.2 wt % at 273 K /1.0 bar) was achieved, which is attributed to the formation of bicarbonate, as there may be the possibility of the presence of little moisture in the system, which facilitates the interaction. These hybrid polymeric materials exhibited a better storage capacity of CO2.

Green synthesis of PLGA and fabrication of topotecan and thymoquinone dual anticancer drug loaded PLGA nanoparticles: a controlled release study for cancer therapy - Srilatha Cheekuramelli, Naga; Muhammed, Hasin N.; Garnaik, Baijayantimala; Sukumaran Nair, Kiran (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2026)
Cancer therapy is often hindered by poor solubility, low bioavailability, drug resistance, and tumor microenvironmental barriers associated with conventional chemotherapeutics. Polymeric nano-drug delivery systems offer a promising strategy to overcome these limitations, particularly for synergistic multi-drug delivery. In this study, a biodegradable and biocompatible PLGA copolymer (70:30, M-w approximate to 14,500) was synthesized by ring-opening polymerization using zinc proline complex as an initiator through a green route. The copolymer's potential for delivering topotecan (TPT), a water-soluble chemotherapeutic, thymoquinone (TQ), a poorly water-soluble chemotherapeutic, and their combination (TPT+TQ) for cancer treatment was investigated. These nanoparticles demonstrateda consistent particle size < 200 nm high encapsulation efficiency along with desirable controlled-release attributes. Moreover, they exhibited specific release characteristics and cytotoxic effects against HeLa cells, achieving an IC50 value of 20.88 M for the combination therapy (TPT+TQ). Additionally, cytocompatibility testing on L929 fibroblasts confirmed over 98% cell viability for blank PLGA nanoparticles. Additionally, confocal imaging studies confirmed efficient cellular uptake and nuclear localization of the nanoparticles. Overall, the PLGA based dual drug loaded nanoparticles presents a promising approach for targeted, synergistic co-delivery, potentially improving efficacy and reducing toxicity in cancer therapy.
Keywords: Biodegradation; dual drug-loading; PLGA copolymer; thymoquinone; Topotecan